KOLOKASI FRASA VERBAL (FI‘IL) DAN PREPOSISI (ḤARF JAR) DALAM SURAT AN-NISA’ PADA TAFSIR AL-MISBAH KARYA M. QURAISH SHIHAB - Waki Ats Tsaqofi; Melfin Iza Farhatun Nazillah; Abdullah Abdullah; Ulil Abshar; Abdullah Maulani (STIQ Amuntai, 2022)
This study focuses on Arabic collocations in general. Arabic has a unique linguistic phenomenon that needs to be understood by itself. The questions that will be studied focus on verbal phrases that collocate with prepositions contained in Surat An-Nisa. The word collocation comes from English, which has the word collocate which means